2015
DOI: 10.1111/jicd.12150
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of locally‐delivered 1% metformin gel in the treatment of intrabony defects in patients with chronic periodontitis: a randomized, controlled clinical trial

Abstract: One percent MF was found to significantly improve clinical and radiographic parameters in intrabony defects in patients with chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 35 publications
5
52
0
Order By: Relevance
“…All clinical studies were RCTs . In all studies, number of subjects ranged between 20 and 70 individuals with age ranging between 25 and 55 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All clinical studies were RCTs . In all studies, number of subjects ranged between 20 and 70 individuals with age ranging between 25 and 55 years.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, number of subjects ranged between 20 and 70 individuals with age ranging between 25 and 55 years. The number of patients lost at follow‐up ranged from 0 to 4 patients in the included studies . All studies reported the percentage of female participants, which ranged between 0% and 51%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations